2012
DOI: 10.2500/ajra.2012.26.3683
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic Alterations in Nasal Mucosa after Sphenopalatine Artery Ligation in Patients with Vasomotor Rhinitis

Abstract: In patients with vasomotor rhinopathy and ITH, improvement in symptoms, nasal resistance, ciliated cell trophism, and MTt was observed after sphenopalatine artery ligation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Similarly, included CPNN and SPNN studies found significant improvements in the mean scores for rhinorrhea, congestion, itching, sneezing, and quality of life up to 21 months postoperatively. 3640 Moreover, our findings corroborate and reaffirm the findings of 2 older systematic reviews conducted by Marshak et al (2016) and Halderman et al (2015) who reported comparable efficacy and safety of EVN and PNN in patients with rhinitis (including allergic rhinitis and NAR). 26,42 Uniquely, our findings support the efficacy and safety of the procedures specifically for NAR patients and include studies that performed CPNN.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, included CPNN and SPNN studies found significant improvements in the mean scores for rhinorrhea, congestion, itching, sneezing, and quality of life up to 21 months postoperatively. 3640 Moreover, our findings corroborate and reaffirm the findings of 2 older systematic reviews conducted by Marshak et al (2016) and Halderman et al (2015) who reported comparable efficacy and safety of EVN and PNN in patients with rhinitis (including allergic rhinitis and NAR). 26,42 Uniquely, our findings support the efficacy and safety of the procedures specifically for NAR patients and include studies that performed CPNN.…”
Section: Discussionsupporting
confidence: 90%
“…They generally have a polygonal shape with about 150‐200 cilia at the of top a big central nucleus and a basal region which is in strict contact with basal membrane through desmosomes (Figure , Panel B). A perinuclear halo or hypercromatic supernulcear stria in ciliated cells is a hallmark of normal function, and its reduction has been put in correlation with severity of vasomotor, inflammatory and infectious nasal diseases Muciparous goblet cell: It is a unicellular gland interposed among the respiratory pseudostratified epithelial cells secreting mucin , that in contact with water originates mucus.…”
Section: Cytological Aspects Of Normal Nasal Mucosamentioning
confidence: 99%
“…From these, we selected and have made reference in the text to the following article types: systematic reviews, n = 3; 8 , 15 , 16 narrative reviews or algorithms, n = 8; 11 , 17 23 randomised controlled trials, n = 3; 24 26 non-randomised controlled studies, n = 4; 1 , 27 29 case series or cohort studies, n = 9; 30 – 38 surveys and audits, n = 5; 9 , 10 , 14 , 39 , 40 cost-effectiveness studies, n = 5; 12 , 13 , 41 43 anatomy studies, n = 6; 44 – 49 case reports, n = 5; 50 – 54 and historical articles, n = 6 2 7 …”
Section: Resultsmentioning
confidence: 99%
“…Both treatments improved nasal resistance and mucociliary transit times, but with a significantly greater benefit ( p < 0.05) for the latter in the endoscopic sphenopalatine artery ligation group. A highly significant change, beneficial for a hypersecreting nose, was noted in nasal cytology studies following ligation 26 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation